CO2 Emissions and Financial Performance of Socially Responsible Firms: An Empirical Survey. (7th December 2012) - Sariannidis, Nikolaos; Zafeiriou, Eleni; Giannarakis, Grigoris; Arabatzis, Garyfallos
ABSTRACT A firm's financial performance is closely related to its environmental behavior. This result is valid especially in the case of socially responsible firms. In the present study a data econometric analysis is conducted based on a GARCH model for socially responsible and conventional firms. According to our findings, the performance of socially responsible firms is negatively related to an increase of global CO2 emissions. The firms' costs for implementing environmental policies and the investors' attitude towards the aforementioned firms may account for our results. Copyright © 2012 John Wiley & Sons, Ltd and ERP Environment.